Measuring the impact of venous leg ulcers on quality of life. - Hareendran, A; Bradbury, A; Budd, J; Geroulakos, G; Hobbs, F; Kenkre, J; Symonds, T (2005)
OBJECTIVE: To identify health-related quality-of-life (HRQoL) issues in patients with venous leg ulcers, with the aim of generating items for a treatment outcome measure. METHOD: Thirty-eight patients with venous leg ulcers were interviewed by a psychologist using a semi-structured guide; they also completed a HRQoL questionnaire (modified Skindex). Data from the questionnaire were examined to explore the impact of venous leg ulcers on patients' lives. Interview transcripts were analysed using qualitative methods to identify additional venous leg ulcer-specific HRQoL items. RESULTS: Skindex scores indicated that older patients had worse HRQoL (p<0.05), as did those with pain and non-healing ulcers. Ulcer duration and size did not correlate with HRQoL. Interviews revealed the following effects of ulceration: pain (80.5%); itching (69.4%); altered appearance (66.7%); loss of sleep (66.6%); functional limitation (58.3%); and disappointment with treatment (50%). Based on the interview transcripts, items were generated and discussed with an expert panel, with a view to including them in a venous leg ulcer-specific HRQoL questionnaire. CONCLUSION: Disease-specific HRQoL outcome measures should be considered when evaluating treatments for venous leg ulcers.